2010
DOI: 10.1128/aac.01602-09
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation Steps during Spiramycin Biosynthesis in Streptomyces ambofaciens : Involvement of Three Glycosyltransferases and Their Interplay with Two Auxiliary Proteins

Abstract: Streptomyces ambofaciens synthesizes spiramycin, a 16-membered macrolide antibiotic used in human medicine. The spiramycin molecule consists of a polyketide lactone ring (platenolide) synthesized by a type I polyketide synthase, to which three deoxyhexoses (mycaminose, forosamine, and mycarose) are attached successively in this order. These sugars are essential to the antibacterial activity of spiramycin. We previously identified four genes in the spiramycin biosynthetic gene cluster predicted to encode glycos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
1
34
0
Order By: Relevance
“…Similarly, other glycosyltransferases have been found to require another auxiliary protein for their activity (39)(40)(41). A recent study showed the role of two auxiliary proteins, Srm6 and Srm28, in the activation of two glycosyltransferases, Srm5 and Srm29, respectively, and both are required for the biosynthesis of spiramycin by Streptomyces ambofaciens (42). Activity of the glycosyltransferase EryCIII, which is required for biosynthesis of the antibiotic erythromycin D, is dependent upon an auxiliary protein, EryCII (43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, other glycosyltransferases have been found to require another auxiliary protein for their activity (39)(40)(41). A recent study showed the role of two auxiliary proteins, Srm6 and Srm28, in the activation of two glycosyltransferases, Srm5 and Srm29, respectively, and both are required for the biosynthesis of spiramycin by Streptomyces ambofaciens (42). Activity of the glycosyltransferase EryCIII, which is required for biosynthesis of the antibiotic erythromycin D, is dependent upon an auxiliary protein, EryCII (43).…”
Section: Discussionmentioning
confidence: 99%
“…Activity of the glycosyltransferase EryCIII, which is required for biosynthesis of the antibiotic erythromycin D, is dependent upon an auxiliary protein, EryCII (43). Although the roles of these auxiliary proteins are not clear, it has been proposed that these auxiliary proteins are required to induce conformational changes of the glycosyltransferases, which consequently activate these enzymes (36,42).…”
Section: Discussionmentioning
confidence: 99%
“…Spiramycins I, II, and III were used as standards for quantification by HPLC. The nomenclature used for the genes of the spiramycin biosynthetic gene cluster is different from the one published earlier (25) but is the one used by Nguyen et al (32).…”
Section: Methodsmentioning
confidence: 99%
“…The two PCR fragments were cloned into the pGEM-T Easy vector and then released by HindIII/EcoRV or EcoRV/NheI digestions. The excisable cassette att3-aac conferring apramycin resistance was excised from pOSV234 (29) by EcoRV digestion. The above-mentioned three fragments were simultaneously ligated with the HindIII/NheI-digested vector pWED2 (30), which confers puromycin resistance to generate an adnAB deletion vector.…”
Section: Methodsmentioning
confidence: 99%